Structural basis of nucleosome transcription mediated by Chd1 and FACT - Farnung, Lucas (Nat Struct Mol Biol, 2021)
Efficient transcription of RNA polymerase II (Pol II) through nucleosomes requires the help of various factors. Here we show biochemically that Pol II transcription through a nucleosome is facilitated by the chromatin remodeler Chd1 and the histone chaperone FACT when the elongation factors Spt4/5 and TFIIS are present. We report cryo-EM structures of transcribing Saccharomyces cerevisiae Pol II−Spt4/5−nucleosome complexes with bound Chd1 or FACT. In the first structure, Pol II transcription exposes the proximal histone H2A−H2B dimer that is bound by Spt5. Pol II has also released the inhibitory DNA-binding region of Chd1 that is poised to pump DNA toward Pol II. In the second structure, Pol II has generated a partially unraveled nucleosome that binds FACT, which excludes Chd1 and Spt5. These results suggest that Pol II progression through a nucleosome activates Chd1, enables FACT binding and eventually triggers transfer of FACT together with histones to upstream DNA.